Effect of feeding different levels of formaldehyde treated sesame cake on nutrients intake, milk production and economic returns in lactating crossbred cows - Bugalia, H L; Chaudhary, J L (The Indian Journal of Animal Sciences, 2011)
Lactating crossbred (Holstein Friesian × Tharparker) cows (15), randomly divided into 3 equal groups were allotted to 3 dietary treatments, viz. T1, green berseem and concentrate containing untreated sesame cake (control); T2, green berseem and concentrate containing 1.0% FA treated (1.0g FA/100g CP) sesame cake; and T3, green berseem and concentrate containing 1.5% FA treated (1.5g FA/100g CP) sesame cake to discuss the effect of feeding formaldehyde treated sesame cake as a bypass protein on nutrients intake, milk production and economic returns in lactating cows. Sorghum stover was fed ad lib. in all the groups. The experiment lasted for 90 days. The DM, DCP and TDN intake per kg metabolic body size were 117.79, 9.66 and 72.78 in T1, 120.95, 9.89 and 75.28 in T2 and 140.81, 10.97 and 87.11 in T3, respectively, which were significant in T3 as compared to T2 and T1. However, DM, DCP and TDN intake in T2 and T1 groups did not show any significant difference. The average milk yield was significantly higher in T3 and T2 (10.21 and 9.80) as compared to group T1 (8.73). The total milk yield during 90 days period was also higher in T3 and T2 (918.90 and 882.0kg) as compared to group T1 (785.70 kg). The average feed cost per kg milk production was Rs.6,32, 5.92 and 6.15 in T1, T2 and T3 groups, respectively, indicating that feeding of formaldehyde treated sesame cake can have beneficial effect in lactating crossbred cows, it may be concluded that FA treated sesame cake @ 1.5g/100g CP in place of untreated sesame cake in the concentrate mixture of lactating crossbred cows can prove economically beneficial.